2009
DOI: 10.1007/s11126-009-9116-4
|View full text |Cite
|
Sign up to set email alerts
|

Parental Combat Injury and Early Child Development: A Conceptual Model for Differentiating Effects of Visible and Invisible Injuries

Abstract: The injuries (physical and emotional) sustained by service members during combat influence all members of a family system. This review used a systemic framework to conceptualize the direct and indirect effects of a service member's injury on family functioning, with a specific focus on young children. Using a meta-ethnographic approach to synthesize the health research literature from a variety of disciplines, this review makes relevant linkages to health care professionals working with injured veterans. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 120 publications
(162 reference statements)
1
21
0
Order By: Relevance
“…Renegotiating parenting roles and responsibilities When parents live with OSIs they can experience a range of invisible issues, such as irritability, emotional unavailability, hostility, and hypervigilance, that are disruptive to family relationships (Arata-Maiers & Stafford, 2010;Cozza, Holmes, & Van Ost, 2013;Cozza & Lieberman, 2007;Danish & Antonides, 2013;Dekel & Goldblatt, 2008;Gewirtz, Pinna, Hanson, & Brockberg, 2014;Gorman, Fitzgerald, & Blow, 2010;Harrison, Albanese, & Berman, 2014;Janke-Stedronsky et al, 2016;Lester & Flake, 2013;Lieberman & Horn, 2013;Palmer, 2008;Reed, Bell, & Edwards, 2011;Sammons & Batten, 2008;Seamone, 2012;Ternus, 2010). These issues can impact a parent's ability to consistently negotiate and meet role expectations and household routines, which typically creates friction among family members as the distress an individual living with an OSI feels reverberates throughout the family (Boricevic Mar sanic, Aukst Margetic, Jukic, Matko, & Grgic, 2014;Campbell, Brown, & Okwara, 2011;Cozza, Holmes, et al, 2013;Lester & Flake, 2013;Lester et al, 2010;Lieberman & Horn, 2013), leaving the family with a lower threshold for everyday stressors .…”
Section: Multiple Impacts Of Parental Osis On Children and Youthmentioning
confidence: 99%
See 3 more Smart Citations
“…Renegotiating parenting roles and responsibilities When parents live with OSIs they can experience a range of invisible issues, such as irritability, emotional unavailability, hostility, and hypervigilance, that are disruptive to family relationships (Arata-Maiers & Stafford, 2010;Cozza, Holmes, & Van Ost, 2013;Cozza & Lieberman, 2007;Danish & Antonides, 2013;Dekel & Goldblatt, 2008;Gewirtz, Pinna, Hanson, & Brockberg, 2014;Gorman, Fitzgerald, & Blow, 2010;Harrison, Albanese, & Berman, 2014;Janke-Stedronsky et al, 2016;Lester & Flake, 2013;Lieberman & Horn, 2013;Palmer, 2008;Reed, Bell, & Edwards, 2011;Sammons & Batten, 2008;Seamone, 2012;Ternus, 2010). These issues can impact a parent's ability to consistently negotiate and meet role expectations and household routines, which typically creates friction among family members as the distress an individual living with an OSI feels reverberates throughout the family (Boricevic Mar sanic, Aukst Margetic, Jukic, Matko, & Grgic, 2014;Campbell, Brown, & Okwara, 2011;Cozza, Holmes, et al, 2013;Lester & Flake, 2013;Lester et al, 2010;Lieberman & Horn, 2013), leaving the family with a lower threshold for everyday stressors .…”
Section: Multiple Impacts Of Parental Osis On Children and Youthmentioning
confidence: 99%
“…A study that examined the impact of warm and caring maternal relationships on the children of PTSD veterans indicated that, as adults, children of PTSD veterans experienced less emotional distress and had a greater capacity for intimacy (Dinshtein et al, 2011). This closeness with the children may lead to friction in the spousal relationship and, in some cases, potential exposure to intimate partner violence (Campbell et al, 2011;Dekel & Goldblatt, 2008;Gorman et al, 2010;McFarlane, 2009;Palmer, 2008;Pearrow & Cosgrove, 2009) and negative impacts on the caregiver's psychological well-being and capacity to meet household maintenance demands (Ahmadi, Azampoor-Afshar, Karami, & Mokhtari, 2011;Cozza, Holmes, et al, 2013;Lester, 2012). …”
Section: Spousal Relationships and Parentingmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Injuries sustained by parents in combat can have a variety of psychological effects on their children. 14 Injuries to 1 child in the family increase the risk of injuries to siblings, especially in the first 3 months after the index child' s trauma. 15 However, there has been little research on the effect of parental injury on children in the civilian setting.…”
mentioning
confidence: 99%